2017
DOI: 10.1016/j.nicl.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Altered structural and functional thalamocortical networks in secondarily generalized extratemporal lobe seizures

Abstract: Structural and functional abnormalities in the thalamocortical network in primary generalized epilepsies or mesial temporal lobe epilepsy have recently been identified by voxel-wise analyses of neuroimaging. However, evidence is needed regarding the profiles of the thalamocortical network in patients with secondarily generalized seizures from focal neocortical sources. We used high-resolution T1-weighted, diffusion-tensor and resting-state functional MR imaging (rs-fMRI) to examine 16 patients with secondarily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…At the behavioural level, it has been suggested in a large systematic review of the literature that patients with generalized seizure semiologies are more likely to become seizure-free with VNS ( Englot et al, 2016 ). Various functional neuroimaging studies ( Ibrahim et al, 2014a , Peng and Hsin, 2017 ), as well as electrophysiological investigations ( Wolf and Beniczky, 2014 ) have conclusively implicated distinct thalamocortical circuitry in the generalization of seizure activities, including those related to the cingulate and insular cortices ( Peng and Hsin, 2017 ). Our findings provide a putative connectomics-informed explanation of clinical observations in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…At the behavioural level, it has been suggested in a large systematic review of the literature that patients with generalized seizure semiologies are more likely to become seizure-free with VNS ( Englot et al, 2016 ). Various functional neuroimaging studies ( Ibrahim et al, 2014a , Peng and Hsin, 2017 ), as well as electrophysiological investigations ( Wolf and Beniczky, 2014 ) have conclusively implicated distinct thalamocortical circuitry in the generalization of seizure activities, including those related to the cingulate and insular cortices ( Peng and Hsin, 2017 ). Our findings provide a putative connectomics-informed explanation of clinical observations in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the voxel-wise statistical results were corrected for multiple comparisons using the “AlphaSim” implemented in REST, based on the Monte Carlo simulation in AFNI ( Song et al, 2011 ). The AlphaSim algorithm implemented in REST is widely used to correct multiple comparisons in previous studies ( Fan et al, 2017 , Peng and Hsin, 2017 ). Since the subjects in our research were all healthy individuals, their differences may not have been significant enough to survive a more stringent correction.…”
Section: Discussionmentioning
confidence: 99%
“…In the last two decades resting-state functional magnetic resonance imaging (resting-state functional MRI) has emerged as a useful method to identify the neuropathological signatures for different subtypes of epilepsy ( Centeno and Carmichael, 2014 ; Chen et al, 2017 ; Gupta et al, 2017 ; Paldino et al, 2017 ; Peng and Hsin, 2017 ; Wang et al, 2017 ). For example, alterations in the default mode network (DMN) and thalamus were detected in childhood absence epilepsy ( Wang et al, 2017 ); The thalamus was shown to be impacted in patients suffering from generalized temporal lobe epilepsy ( Peng and Hsin, 2017 ), while the basal ganglia was strongly implicated in frontal lobe epilepsy ( Dong et al, 2016a , Dong et al, 2016b ). For patients with juvenile myoclonic epilepsy (JME) functional connectivity disturbances in both the thalamo-motor and thalamo-frontal networks were found ( Dong et al, 2016b ; Jiang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%